Tribute to Doctor Álvaro Fernández Pérez - Negret, Alvaro (Revista Novedades Colombianas, 1997)
Doctor Álvaro Fernandez Pérez was born in the city of Popayan on February 11, 1920 and there he studied his primary and secondary education. He obtained a baccalaureate degree in the now-defunct National High School of Boys of the Universidad del Cauca and later traveled to Bogotá to continue his studies at the National University of Colombia. He studied pharmacy, obtaining the degree of Chemist-pharmacist and advanced the Doctorate studies offered by the National University in 1945. In the same year he joined the Institute of Natural Sciences of the National University to carry out systematic botany courses that guided the famous Doctor Armando Dugand, which were decisive for his training and for definitely change the direction of their professional activities.